A Case of Respiratory Epithelial Adenomatoid Hamartoma (REAH) in a Patient with History of Radiation Exposure - Darshan N. Patel; Yekaterina A. Koshkareva; Miles McFarland; Nathan A. Deckard (Case Reports in Otolaryngology)
Respiratory epithelial adenomatoid hamartomas (REAHs) are becoming a more commonly recognized otolaryngologic tumor and are often misdiagnosed as inverted papilloma. Here, we present such a case in a patient with history of previous radiation exposure. Otolaryngologists and pathologists should be aware of the mucinous histological appearance of REAH to help differentiate from other growths. Given our patient’s history, an association between REAH and previous radiation exposure is worth consideration.